Laparoscopic surgery in treatment of patients with endometrial cancer and obesity - A. I. Berishvili; K. P. Laktionov; T. M. Kochoyan; S. B. Polikarpova; N. V. Levkina (ABV-press, 2014)
The paper evaluates the role and place of laparoscopic surgery in treatment of patients with endometrial cancer and obesity. It describes the types of similar operations: laparoscopic hysterectomy ± pelvic lymphadenectomy. Overall and disease-free survival is reported to be the same with both laparoscopy and open surgery.